Phase segregation in mixed-halide perovskites affects charge-carrier dynamics while preserving mobility - Motti, SG; Patel, JB; Oliver, RDJ; Snaith, HJ; Johnston, MB; Herz, LM (Springer Nature, 2021)
Mixed halide perovskites can provide optimal bandgaps for tandem solar cells which are key to improved cost-efficiencies, but can still suffer from detrimental illumination-induced phase segregation. Here we employ optical-pump terahertz-probe spectroscopy to investigate the impact of halide segregation on the charge-carrier dynamics and transport properties of mixed halide perovskite films. We reveal that, surprisingly, halide segregation results in negligible impact to the THz charge-carrier mobilities, and that charge carriers within the I-rich phase are not strongly localised. We further demonstrate enhanced lattice anharmonicity in the segregated I-rich domains, which is likely to support ionic migration. These phonon anharmonicity effects also serve as evidence of a remarkably fast, picosecond charge funnelling into the narrow-bandgap I-rich domains. Our analysis demonstrates how minimal structural transformations during phase segregation have a dramatic effect on the charge-carrier dynamics as a result of charge funnelling. We suggest that because such enhanced recombination is radiative, performance losses may be mitigated by deployment of careful light management strategies in solar cells.